(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The utilization of 3-Dimensional (3D) porous textile materials by the civil and mechanical engineers for improved thermo-acoustic environment has widened the research scope. Unconventional three-dimensional textile material which grabs the attention of the researchers for multi-functional applications is spacer fabrics. Since spacer fabrics have superior thermal and acoustic characteristics compared to conventional woven/knitted structures or nonwovens due to their wonderful 3D porous nature. It has two outer layer connected with the help of monofilament or multifilament spacer yarn which kept the fabric bulkier with low density and highly breathable. Due to porous nature, interconnected pores, bulkier and 3D structure, the spacer fabrics have ability to attenuate more sound energy than the conventional materials. This research paper presents an experimental investigation on the sound absorption behaviour and thermal properties of warp knitted spacer fabrics. The Sound absorption coefficient (SAC) and thermal conductivity (K) were measured using two microphone impedance tube and Alambeta. This study deeply discusses the influence of material parameters and characteristics on acoustic properties of 3D spacer knitted fabrics. The results show that the fabric surface property, porosity, flow resistivity and tortuosity have significant effects on the sound absorption as well as thermal conductivity. With the obtained results, this work derives regression equations and correlation between noise absorption and thermal properties of spacer fabrics.